Sex Differences in the Effects of Mental Work and Moderate-Intensity Physical Activity on Energy Intake in Young Adults. (29th May 2013) - Pérusse-Lachance, Emilie; Brassard, Patrice; Chaput, Jean-Philippe; Drapeau, Vicky; Teasdale, Normand; Sénécal, Caroline; Tremblay, Angelo
Abstract : The aim of this study was to examine the acute effects of mental work and moderate-intensity physical activity on various components of energy balance in young and healthy adults. With the use of a randomized crossover design, 35 participants aged 24 ± 3 years completed three 45-min conditions, namely, (i) resting in a sitting position (control), (ii) reading and writing (mental work (MW)), and (iii) exercising on a treadmill at 40% of peak oxygen uptake (exercise), followed by an ad libitum lunch. The endpoints were spontaneous energy intake (EI), energy expenditure (EE), appetite sensations, and EI for the remainder of the day. We observed that the energy cost of the control and MW conditions was about the same whereas the exercise condition increased EE to a greater extent in men than women. Exercise induced a decrease in EI relative to EE compared to the control condition that was more pronounced in men than women. However, women tended to increase their energy intake after the MW condition compared to the control one whereas an opposite trend was observed in men. None of the appetite sensation markers differed significantly between both sexes. In conclusion, men and women have specific food intake patterns when submitted to cognitive and physical stimuli.